Understanding continued use of smart learning platforms: psychological wellbeing in an extended TAM-ISCM model - Li, Jinlei; Jin, Meilin; Chen, Xiaowei (Frontiers in Psychology, 2025)
IntroductionIn response to the growing adoption of digital education technologies, this study explores the factors influencing the continuous use of innovative learning platforms among students in higher vocational education. Recognizing that technological performance and psychological experiences shape user engagement, this research extends the Technology Acceptance Model (TAM) by integrating constructs such as perceived trust, enjoyment, ideological alignment, and psychological states—including satisfaction, wellbeing, and anxiety.MethodsData were collected from 782 higher vocational college students in China using an online questionnaire. Participants represented diverse academic fields (e.g., liberal arts, sciences, engineering, arts) and were balanced in terms of gender (44.28% male and 55.72% female). Structural Equation Modeling (SEM) was applied to assess direct and indirect relationships among key variables, including perceived usefulness, perceived ease of use, system quality, expectation confirmation, enjoyment, and psychological indicators such as anxiety and subjective wellbeing. The mediating role of psychological wellbeing was also tested to evaluate its influence on continued platform usage.ResultsPerceived enjoyment emerged as the strongest predictor of continuance intention (β = 0.52, p < 0.001), underscoring the central role of affective engagement in promoting sustained platform use. Perceived usefulness (β = 0.38, p < 0.01) and expectation confirmation (β = 0.31, p < 0.01) also exerted significant positive effects, supporting the cognitive appraisal mechanisms outlined in TAM and Expectation-Confirmation Theory. Interestingly, perceived trust negatively affected satisfaction (β = −0.13, p < 0.05), possibly due to a mismatch between institutional trust and user expectations, which may lead to psychological strain. System quality had no significant impact on satisfaction (β = 0.05, p > 0.05), suggesting that users view platform reliability as a baseline requirement rather than a satisfaction driver. Moreover, psychological wellbeing—defined by higher satisfaction and lower anxiety—is mediated between platform experience and continued use.DiscussionThese findings highlight the need for innovative learning platforms to address technological expectations and psychological resilience. While usability and usefulness remain essential, designers must foster emotional engagement and manage trust-based expectations. Platforms that overlook psychological dimensions risk diminishing user satisfaction and long-term retention.ConclusionSustaining engagement with innovative learning platforms in higher vocational education requires a holistic approach that balances functional usability with mental wellbeing. This study offers important theoretical and practical insights for educators, developers, and policymakers aiming to create emotionally supportive and pedagogically effective digital learning environments.